2023
DOI: 10.1371/journal.pone.0294669
|View full text |Cite
|
Sign up to set email alerts
|

A global exploratory comparison of country self-citations 1996-2019

Alberto Baccini,
Eugenio Petrovich

Abstract: Self-citations are a key topic in evaluative bibliometrics because they can artificially inflate citation-related performance indicators. Recently, self-citations defined at the largest scale, i.e., country self-citations, have started to attract the attention of researchers and policymakers. According to a recent research, in fact, the anomalous trends in the country self-citation rates of some countries, such as Italy, have been induced by the distorting effect of citation metrics-centered science policies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 120 publications
(194 reference statements)
0
4
0
Order By: Relevance
“…Future studies should also extend this analysis beyond the G10 countries as done by Baccini and Petrovich (2023) in the study of self-citations. Indeed, Baccini et al (2023) demonstrated that Italy is the sole G10 country experiencing a recent surge in self-citations diverging from the other countries since 2010.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Future studies should also extend this analysis beyond the G10 countries as done by Baccini and Petrovich (2023) in the study of self-citations. Indeed, Baccini et al (2023) demonstrated that Italy is the sole G10 country experiencing a recent surge in self-citations diverging from the other countries since 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should also extend this analysis beyond the G10 countries as done by Baccini and Petrovich (2023) in the study of self-citations. Indeed, Baccini et al (2023) demonstrated that Italy is the sole G10 country experiencing a recent surge in self-citations diverging from the other countries since 2010. The year 2010 marks the initiation of a government reform (Law 240/2010) in the Italian university system when algorithms were introduced to reward researchers based on the number of citations they received.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the late 1980s, numerous European and non-European countries have implemented national systems to monitor, assess, and evaluate the research performance of their scientific workforce ( Hicks, 2012 , Baccini et al, 2019 , Baccini and Petrovich, 2023 ). A prominent feature of these research evaluation systems is the emphasis on quantitative indicators, recognized as pivotal science policy tools ( Ingwersen & Larsen, 2014 ).…”
Section: Introductionmentioning
confidence: 99%